FAKTOR-FAKTOR YANG MEMPENGARUHI KESULITAN BELAJAR PADA SISWA KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN - Karuniawati Astuti; Tuti Iriani; Santoso Sri Handoyo (Jurnal Pensil : Pendidikan Teknik Sipil, 2015)
This study aims to determine the factors that influence students' learning difficulties On Skill Of Competency Architecture Engineering (Case Study at SMK Negeri 4 South Tangerang) academic year 2043/2015. The research lasted for 2 months from Marct to April 2015.In this study, the writer uses the survey method. The population in this study was the architecture engineering students of grade X year 2014/2015, a total of 71 students. The data collection tool used in this study was a questionnaire. Trial questionnaire instrument conducted by15 respondents majoring in class XI skill of competency architecture engineering. The analysis of instrument trial and error was conducted on the validity and reliability (Cronbach Alpha), for the number of fixed statement items is 25 items and the reliability result r11 = 0.91.Based on the data from the percentage of the number of students, the results of this study indicate that the factors affecting students' learning difficulties are largely on the internal factors which are psychological factor indicators with sub readiness of students (over 51%) and subtalent of students (over 50%). Meanwhile, the external factors that affect students' learning difficulties are largely on the indicators of school environmental factors with sub methods used by teachers (over 50%) and sub relationships between students (over 50%).